Algoritma Needleman-Wunsch dalam Menentukan Tingkat Kemiripan Urutan DNA Rusa Timor (Cervus timorensis) dan Rusa Merah (Cervus elaphus) - Hibban Kholiq; Mamika Ujianita Romdhini; Marliadi Susanto (University of Mataram, 2020)
Sequence alignment is a basic method in sequence analysis. This method is used to determine the similaritiy level of DNA sequences. The Needleman-Wunsch algorithm is an algorithm that can be used to solve the problem of sequence alignment. This research shows that the relation T (i, j) used in the Needleman-Wunsch algorithm is a function where T: (ℕ0 ℕ0) → ℤ. The function T (i, j) is a recursive function. Moreover, DNA sequence data used are DNA sequences from the Timor Deer, which are the identities of the provinces of West Nusa Tenggara and Red Deer, which are typical deer from the European continent as a comparison. The DNA sequence data was obtained from BLAST (Basic Local Alignment Search Tool). Based on the alignment, the most optimal alignment is obtained by forming 666 base pairs sequences with 322 matches, 230 missmatches and 114 gaps, meaning that the two DNA sequences have a 48% similarity (322/666).